Next generation sequencing of the cellular and liquid fraction of pancreatic cyst fluid supports discrimination of IPMN from pseudocysts and reveals cases with multiple mutated driver clones: First findings from the prospective ZYSTEUS biomarker study. Issue 1 (17th October 2018) - Volckmar, Anna‐Lena; Endris, Volker; Gaida, Matthias M.; Leichsenring, Jonas; Stögbauer, Fabian; Allgäuer, Michael; von Winterfeld, Moritz; Penzel, Roland; Kirchner, Martina; Brandt, Regine; Neumann, Olaf; Sültmann, Holger; et al.
Abstract: Approximately half of all pancreatic cysts are neoplastic, mainly comprising intraductal papillary mucinous neoplasms (IPMN), which can progress to invasive carcinoma. Current Fukuoka guidelines have limited sensitivity and specificity in predicting progression of asymptomatic pancreatic cysts. We present first results of the prospective ZYSTEUS biomarker study investigating (i) whether detection of driver mutations in IPMN by liquid biopsy is technically feasible, (ii) which compartment of IPMN is most suitable for analysis, and (iii) implications for clinical diagnostics. Twenty‐two patients with clinical inclusion criteria were enrolled in ZYSTEUS. Fifteen cases underwent endoscopic ultrasound (EUS)‐guided fine‐needle aspiration and cytological diagnostics. Cellular and liquid fraction of the cysts of each case were separated and subjected to deep targeted next generation sequencing (NGS). Clinical parameters, imaging findings (EUS and MRI), and follow‐up data were collected continuously. All IPMN cases ( n  = 12) showed at least one mutation in either KRAS ( n  = 11) or GNAS ( n  = 4). Three cases showed both KRAS and GNAS mutations. Six cases harbored multiple KRAS / GNAS mutations. In the three cases with pseudocysts, no KRAS or GNAS mutations were detected. DNA yields were higher and showed higher mutation diversity in the cellular fraction. In conclusion, mutation detection in pancreatic cyst fluid is technically feasible with more robust results in the cellular than in the liquid fraction. Current results suggest that, together with imaging, targeted sequencing supports discrimination of IPMN from pseudocysts. The prospective design of ZYSTEUS will provide insight into diagnostic value of NGS in preoperative risk stratification. Our data provide evidence for an oligoclonal nature of IPMN.